Understanding action research in pedagogical practice and teacher training: In memoriam Ágnes Vámos - Zank, Ildikó (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Action research creates favourable conditions for true collaboration, connecting theory and practice, making it possible for the professional community to integrate and apply various types of knowledge. The paper provides a brief overview of the history of action research, of the way it is embedded in a pedagogical context, and of its possible role in teacher training with a view particular to the developments of the Pécs educational science initiative. By drawing a parallel between the criteria of the cooperative principle and educational action research, the paper discusses the possibility of a paradigmatic interpretation, and also seeks to defi ne the quality criteria of action research.